2013
DOI: 10.4103/0972-124x.107489
|View full text |Cite
|
Sign up to set email alerts
|

Severe periodontitis associated with chronic kidney disease

Abstract: The data on Indian population with regard to severity/prevalence of chronic periodontitis in association with chronic kidney disease (CKD) is scarce. We are describing an interesting case of severe periodontitis associated with CKD. The patient had unusual inflammatory gingival overgrowth which persisted even after treatment. By describing this case we want to highlight our current lack of understanding with regard to etiopathogenesis of periodontal disease in CKD patients and need for further research in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Significant prevalence of periodontitis is reported to be associated with systemic conditions such as diabetes mellitus,[ 17 38 39 ] arthritis, CVD, respiratory diseases, kidney disease is in concordance with other studies[ 40 41 ] and the current study has also confirmed this association.…”
Section: Discussionsupporting
confidence: 93%
“…Significant prevalence of periodontitis is reported to be associated with systemic conditions such as diabetes mellitus,[ 17 38 39 ] arthritis, CVD, respiratory diseases, kidney disease is in concordance with other studies[ 40 41 ] and the current study has also confirmed this association.…”
Section: Discussionsupporting
confidence: 93%
“…An earlier case report regarding severity of PD and inflammatory gingival enlargement in CKD patient showed a lack of response to nonsurgical periodontal treatment. [ 20 ] It was decided to manage the case surgically after obtaining patient consent and in coordination with patient's nephrologist. Healing was uneventful and the periodontal status was significantly improved without any sign of recurrence within 6 months of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CKD patients have higher levels of traditional systemic in lammatory markers, like IL-6, and C-reactive protein. Many studies have reported increased prevalence and severity of periodontal disease in patients with CKD (Jain and Kabi, 2013). Free radicals are mostly involved in the destruction of periodontium during various stages of in lammatory periodontal diseases.…”
Section: Resultsmentioning
confidence: 99%